Cardiomyocyte Reprogramming: A Potential Strategy for Cardiac Regeneration - Tendean, Marshel; Oktaviono, Yudi Her; Sandra, Ferry (Molecular and Cellular Biomedical Sciences, 2017)
Heart disease is the leading cause of death worldwide. Within decades a limited process of cardiac cell regeneration was under observation. Embryonic stem cell (ESC) shows great potential for cell and tissue regeneration. Studies indicate that ESC has the potential to enhance myocardial perfusion and/or contractile performance in ischemic myocardium. However there is still challenge to evaluate the issues of teratoma. Then induced pluripotent stem cell was invented by introducing four transcriptional factors (Oct4, Sox2, Klf4, c-Myc). iPSC was created from murine fibroblast and then differentiated into cardiomyocyte. Reprogramming the adult cell could be performed in full, partial or direct reprogramming. Several studies add the significance by reprogramming the cells through more efficient techniques. However several limitations are still remained.Keywords: cardiomyocyte, reprogramming, iPSC, fibroblast